A retrospective multicenter study comparing the punctures to B2 and B3 in endoscopic ultrasound–guided hepaticogastrostomy - Masanari Sekine; Yusuke Hashimoto; Taro Shibuki; Kei Okumura; Ikuhiro Kobori; Aki Miyagaki; Yoshihiro Sasaki; Yuichi Takano; Keita Matsumoto; Hirosato Mashima (DEN Open)
Abstract Objectives In recent years, endoscopic ultrasound–guided hepaticogastrostomy (EUS–HGS) has been performed as an important salvage option for failed endoscopic retrograde cholangiopancreatography for biliary drainage. However, technical issues, such as puncture site (bile duct of segment 3 [B3] or bile duct of segment 2 [B2]), dilation method, stent selection, and procedural safety, need to be resolved for the optimization of EUS–HGS. The present study was to compare the safety, difficulty, and technical and functional success between biliary access via B2 and B3 during EUS–HGS. Methods We conducted a retrospective investigation of 161 consecutive EUS–HGS cases across a total of 6 facilities, including those at our hospital. The patients were divided into two groups according to the successful drainage route: the puncture to B2 (P‐B2) or the puncture to B3 (P‐B3). We compared the technical and functional success rates, technical difficulty, and adverse events between the two groups. We also conducted a subgroup analysis to show the factors related to the procedure time. Results There were 92 cases in the P‐B2 group and 69 cases in the P‐B3 group. There were no significant differences in the technical success, functional success, or adverse events between the groups; however, the procedure time was significantly shorter in P‐B2 cases than in P‐B3 cases. The multivariate analysis showed that the puncture site was the only factor related to the procedure time. Conclusions Based on these findings, P‐B2 appears useful and safe. P‐B2 is as effective as P‐B3 and was able to be performed in a shorter period of time. The B2 approach can be considered a useful option for EUS–HGS.